2004
DOI: 10.1364/josaa.21.000306
|View full text |Cite
|
Sign up to set email alerts
|

Museum lighting: Why are some illuminants preferred?

Abstract: We had shown earlier that viewers prefer to look at artworks under illuminants of approximately 3600 K. In the latest paper we tested the hypothesis that the preferred illuminant is one that appears neither warm nor cool and repeated the settings at each of four illuminances to test the stability of the findings. Observers looked at a neutral white reflectance standard hung on a matte-gray wall lit by overhead banks of lamps whose combined value could be adjusted continuously between 3000 and 4400 K while illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…Furthermore, the appearance of blues are often more sensitive to lighting properties than other colors. 22 Including this range of blues is a significant difference when compared with research using printed reproductions 5,6,12,14 in which phthalocyanine blue is used exclusively, a pigment that is fairly robust to changes in lighting.…”
Section: Artist Materials Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the appearance of blues are often more sensitive to lighting properties than other colors. 22 Including this range of blues is a significant difference when compared with research using printed reproductions 5,6,12,14 in which phthalocyanine blue is used exclusively, a pigment that is fairly robust to changes in lighting.…”
Section: Artist Materials Datasetmentioning
confidence: 99%
“…Advances in reflector properties have led to incandescent tungstenhalogen multifaceted reflector (MR) lamps that can achieve CCTs of 5000 K. 4 Thus, it is possible to use conventional spot illumination with a range of CCTs. Scuello et al 5,6 performed visual experiments evaluating printed reproductions of artwork; they found that observers preferred a CCT of 3600 K for lighting ranging between 2500 and 7000 K at an illuminance of 200 lx. The dominant lighting for the display of art remains natural daylight and incandescent.…”
Section: Introductionmentioning
confidence: 99%
“…Illumination is the deliberate use of light emitted from a source (or multiple sources) to achieve a practical or aesthetic effect, such as indoor lighting, outdoor lighting, automotive lighting, etc . In practical applications, it may require different distributions of light to achieve different lighting effects.…”
Section: Introductionmentioning
confidence: 99%
“…For meat display lighting, rose light can be used to reduce the discoloration of meat; for illuminating white fish, sparkling white light can be used to make fish look fresh. On the other hand, in museums, illuminating artworks is an important issue that should be considered by designers [1][2][3]. The psychophysical experiment results reported in [1] show that observers prefer bluish white light for looking at displayed artworks.…”
Section: Introductionmentioning
confidence: 99%
“…The psychophysical experiment results reported in [1] show that observers prefer bluish white light for looking at displayed artworks. However, the psychophysical experimental results in [2] suggest that the CCT of the illuminant that observers prefer is 3600 K. Because of their high controllability and high color saturation, colored LEDs can be mixed flexibly to generate white light and to enhance the color appearance of illuminated objects. In [3], the authors calculate the a and b chroma of different color patches under different LED illuminations.…”
Section: Introductionmentioning
confidence: 99%